Recent advances in : Cardiology 17 - Rowlands, Derek; Clarke, Bernard (London : Medical publishers, 2015)
Proporciona una selección de artículos de revisión que presentan importantes avances en el campo de la medicina cardíaca. Escrito por expertos de renombre y que cubre temas como la muerte súbita cardíaca en adultos jóvenes, biomarcadores y estratificación de riesgo y VIH y enfermedad coronaria, Avances recientes en cardiología: 17 es una lectura esencial para los médicos en formación y médicos cardíacos en ejercicio que desean mantenerse al día con las últimas novedades desarrollados en este campo.
Chapter 1 The impact of south asian ethnicity on the incidence and prognosis of coronary disease Chapter 2 Sudden and/ or unexpected cardiac death in young adults Chapter 3 Out-of hospital cardiac arrest: survival, immediate and long-term mangement, and strategies for improvement Chapter 4 Cardiac biomarkers and risk stratification Chapter 5 HIV and coronary heart disease Chapter 6 Percutaneous valve intervention Chapter 7 The eldrly patient with aortic stenosis Chapter 8 Heart failure with preserved ejection fraction Chapter 9 Targeting BMPR-II deficiency for treatment of pulmonary arterial hypertension Chapter 10 Inappropriate sinus tachycardia
Incluye índice de contenido
Incluye bibliografía
Keywords: CARDIACOS; VIH -- CORAZÓN; CORAZÓN -- ENFERMEDADES